The centipede genus Newportia Gervais, 1847, in Mexico: description of a new troglomorphic species; redescription of N. sabina Chamberlin, 1942; revival of N. azteca Humbert & Saussure, 1869; and a summary of the fauna (Scolopendromorpha: Scolopocryptopidae: Newportiinae) - Chagas Junior, Amazonas; Shelley, Rowland M. (Zootaxa, 2003)
In Mexico, the newportiine scolopocryptopid genus Newportia Gervais, 1847, comprises 10 species: N. mexicana (Saussure, 1858); N. azteca Humbert & Saussure, 1869; N. stolli (Pocock, 1896); N. spinipes Pocock, 1896; N. oreina Chamberlin, 1915; N. sabina and pelaezi, both by Chamberlin, 1942; N. atoyaca and morela, both by Chamberlin, 1943, and N. troglobia, n. sp. The last occurs in caves in Tamaulipas and appears to be an obligate troglobite; N. sabina, known only from caves in San Luis Potosi, is redescribed and illustrated. Newportia azteca is revived and returned to its rightful position as the third oldest name in the genus; despite having priority by 27 years, it had been considered to be “the same” as N. spinipes and dropped from nomenclature. Although Newportia and the Newportiinae are not known from the continental United States, they do inhabit the country’s territories in the Caribbean; N. heteropoda Chamberlin, 1918, is reported from Puerto Rico, and N. longitarsis virginiensis Lewis, 1989, is recorded from St. Thomas and St. Croix, US Virgin Islands, and Tortola and Virgin Gorda, British Virgin Islands. The northernmost Mexican record, of N. pelaezi in Nuevo León, is only 96 mi (154 km) south of the US border, suggesting that the taxa may potentially be discovered in the southern periphery of Texas; likewise, rafting from Cuba, where 4–5 species occur, could bring them to the Florida Keys. New localities from Mexico are presented for N. stolli, N. spinipes, N. oreina, N. atoyaca, and N. morela, and ranges are depicted on a distribution map.